Terminologi Pemuridan Dalam Injil Matius 28:19-20 - Arman Susilo; Nova Huwae (Predica Verbum: Jurnal Teologi dan Misi, 2022)
The term disciple in Matthew 28:19 has a deep theological meaning. The term inspired the birth of the missionary work carried out by the church. As a result, the church continues to grow throughout the world. Uniquely, the command to make disciples is only recorded by the Gospel of Matthew, not recorded in the other two Synoptic Gospels. It is necessary to carry out an in-depth study of the concept of discipleship recorded by Matthew. In addition, there are some grammatical errors that Matthew uses, giving rise to a prejudice that the idea in Matthew 28:16-20 is invalid. Then, the long period of time between the events recorded and the year of writing is also a special problem in responding to the idea of ​​making disciples of nations. Allegedly, the author's motivation is the key in understanding the use of the term "matheteusate". The study of the grammatical elements, the historical and cultural context of the Jews as well as historiographical observations are relevant ways in finding the reason why Matthew uses the term, "matheteusate" at the end of his Gospel. This study aims to find the basic idea used by Matthew in relation to the term “disciple the nations”. As a result, readers of the Gospel of Matthew will not be trapped in a Christian mission methodology, but will understand the nature of the Christian mission inherited by Jesus himself.